2014
DOI: 10.1007/s11099-014-0030-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil water availability on photosynthesis in Ziziphus jujuba var. spinosus in a sand habitat formed from seashells: Comparison of four models

Abstract: The photosynthetic and chlorophyll fluorescence parameters were studied in Ziziphus jujuba var. spinosus under different soil water gradients obtained by irrigation and natural water consumption. We used the rectangular hyperbola model, the nonrectangular hyperbola model, the exponential model, and the modified rectangular hyperbola model to fit our data and evaluate them quantitatively. Based on the relationship among the parameters, the effects of the availability of soil water on photosynthesis were elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…On the global scale, GPP changes by 4.7 % 0.01 −1 and NPP by 5.5 % 0.01 −1 in response to soil wetness. Although experiments also show rapid reductions in carbon assimilation due to drought stress (e.g., Ruehr et al, 2012;Xia et al, 2014), the magnitude of such influence is difficult to evaluate because different metrics and depths of soil water are used in measurements. Isoprene emissions from PS_BVOC show similar soil-wetness responses to that of GPP (Fig.…”
Section: Impacts Of Meteorologymentioning
confidence: 99%
“…On the global scale, GPP changes by 4.7 % 0.01 −1 and NPP by 5.5 % 0.01 −1 in response to soil wetness. Although experiments also show rapid reductions in carbon assimilation due to drought stress (e.g., Ruehr et al, 2012;Xia et al, 2014), the magnitude of such influence is difficult to evaluate because different metrics and depths of soil water are used in measurements. Isoprene emissions from PS_BVOC show similar soil-wetness responses to that of GPP (Fig.…”
Section: Impacts Of Meteorologymentioning
confidence: 99%
“…The MRHM fitted the P Nmax and the LSP well, and the NRHM fitted the RD, the AQY, and the LCP. These data indicated that the MRHM is suitable for light-response parameters at high light intensities and the NRHM is suitable for response parameters at low light intensities (Xia et al, 2014). Therefore, the MRHM its advantages still hold when applied to citrus plants under different rootstocks conditions.…”
Section: Discussionmentioning
confidence: 89%
“…The order of the models from best to worst fit was consistent with the results of studies on Ziziphus jujuba var. spinosus (Xia et al, 2014) and winter wheat (Li et al, 2011). The MRHM fitted the P Nmax and the LSP well, and the NRHM fitted the RD, the AQY, and the LCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it seemed that photoinhibition can be well described by the Binom model, the fitted Ic values were negative, which was out of the common sense (Ye and Yu 2007, Zheng et al 2012. The modified rectangular hyperbola model (Ye 2007, Ye and Yu 2008b, Lobo et al 2013, Fang et al 2015, called the Ye model, can solve the above problems and show a better simulation results than other models (Ye 2007, Zheng et al 2012, Lang et al 2013, Xia et al 2014.…”
Section: Introductionmentioning
confidence: 99%